Is twice the duration of washout sufficient time between multiple breath nitrogen washout tests?. Issue 2 (2nd February 2017) - Hardaker, Kate M.; Gustafsson, Per; Cooper, Peter; Fitzgerald, Dominic; Selvadurai, Hiran; Robinson, Paul D.
Multiple breath washout (MBW) assesses both lung volume (functional residual capacity (FRC)) and ventilation inhomogeneity (lung clearance index (LCI)). The latter's insight into underlying lung pathology and response to intervention has triggered a recent MBW resurgence [1–4]. Validated commercial equipment has become available [5 ], increasing suitability for widespread use, and a European Respiratory Society/American Thoracic Society endorsed MBW consensus statement has been published to guide manufacturers and operators [6]. This document highlights the need for further evidence across several recommendation areas. In the May 2015 issue of this journal Salamon et al. [7] tackled one such important issue: what duration should be employed between two MBW tests within a testing session? Previous recommendations of gaps of ≥15 min in healthy and ≤60 min in obstructed patients [8] were shown to be too conservative . Using a gap of the previous washout duration led to 10% lower FRC values (p<0.001) but no effect was observed if this was doubled, in line with the recent consensus-based recommendation. [9]. The results presented here address two important limitations to the data presented by Salamon et al. [7], as acknowledged by the authors themselves, to further strengthen the recommendation's evidence base. First, in their paediatric cohort, an alternate, fixed-gap duration protocol was used (5 and 15 min), which translated to an excessive duration between tests (mean 2.6×). Secondly, LCI data was not reported, which may have compromised the ability to detect any detrimental effects. A wait time between MBNW tests of twice the washout duration has no detrimental effect on LCI and FRC outcomes http://ow.ly/RF8y304V3PB